Rpm2, the protein subunit of mitochondrial RNase P in Saccharomyces cerevisiae, also has a role in the translation of mitochondrially encoded subunits of cytochrome c oxidase. - Stribinskis, V (2001)
RPM2 is a Saccharomyces cerevisiae nuclear gene that encodes the protein subunit of mitochondrial RNase P and has an unknown function essential for fermentative growth. Cells lacking mitochondrial RNase P cannot respire and accumulate lesions in their mitochondrial DNA. The effects of a new RPM2 allele, rpm2-100, reveal a novel function of RPM2 in mitochondrial biogenesis. Cells with rpm2-100 as their only source of Rpm2p have correctly processed mitochondrial tRNAs but are still respiratory deficient. Mitochondrial mRNA and rRNA levels are reduced in rpm2-100 cells compared to wild type. The general reduction in mRNA is not reflected in a similar reduction in mitochondrial protein synthesis. Incorporation of labeled precursors into mitochondrially encoded Atp6, Atp8, Atp9, and Cytb protein was enhanced in the mutant relative to wild type, while incorporation into Cox1p, Cox2p, Cox3p, and Var1p was reduced. Pulse-chase analysis of mitochondrial translation revealed decreased rates of translation of COX1, COX2, and COX3 mRNAs. This decrease leads to low steady-state levels of Cox1p, Cox2p, and Cox3p, loss of visible spectra of aa(3) cytochromes, and low cytochrome c oxidase activity in mutant mitochondria. Thus, RPM2 has a previously unrecognized role in mitochondrial biogenesis, in addition to its role as a subunit of mitochondrial RNase P. Moreover, there is a synthetic lethal interaction between the disruption of this novel respiratory function and the loss of wild-type mtDNA. This synthetic interaction explains why a complete deletion of RPM2 is lethal.